Enzymatic Method for the Determination of Paroxetine by Oxidative Coupling with Orcinol - FELICE CHORAGUDI, SHECHINAH; KRANTHI, T.; RADHA RANI, V.; SYAMALA, B.; JAYACHANNDRA, I. (Asian Journal of Chemistry, 2010)
A novel enzymatic method for routine determination of paroxetine in pharmaceutical formulations and bulk dosage forms is proposed. This enzymatic method is based on the formation of coloured species on oxidative coupling of paroxetine with orcinol which undergoes prior oxidation in the presence of Horse radish peroxidase. The resulting pink coloured chromogen shows maximum absorption at lmax 750 nm. Results of analysis were validated statistically and by recovery studies. Assay and recovery studies were also performed. The molar absorptivity was found to be 0.67 × 104 L mol-1 cm-1 and the % RSD of the method was found to be 0.17.